PERANCANGAN APLIKASI PELAYANAN ADMINISTRASI PADA DESA BALIDA YANG TERINTEGRASI E-KTP BERBASIS WEB - Harun Sujadi; Nunu Nurdiana; Ardi Mardiana; Intan Kusumadewi (INFOTECH journal, 2022)
Currently the development of technology is very rapid and has a role to help every human activity. One of the results of technological developments is radio frequency-based technology, RFID (Radio Frequency Identification). Utilization of RFID used on electronic identity cards (e-KTP) is a resident identity card equipped with a chip which is the official identity of the population as proof of self issued by the implementing agency. The administrative service process in most villages still uses conventional methods, one of which is Balida village. The process of administrative services such as making letters, within a week many people apply. so that public dissatisfaction with services arises, causing crowds, considering the covid-19 pandemic has entered Indonesia, people are required to comply with health protocols and avoid crowds. Therefore, the author initiated a system design to serve administrative services in the village of Balida to comply with the health protocol. The programming used for this application is PHP and uses the Laravel framework and MySQL as the database. The purpose of this study is to design an application for administrative services in Balinese villages that is integrated with e-KTP. The development method used is RUP. The result of the application of this administrative service application is that people who have an e-KTP can use it for letter administration.